Evaluation of scented rice genotypes and fungicides against blast and compatibility of pesticides used against neck blast, stem borer and leaf folder - L. RAM; RATTAN SINGH, RAM SINGH*, S. SUNDER, D.S. DODAN (Indian Phytopathology, 2010)
Out of 119 scented rice genotypes, twenty-seven were found consistently resistant to leaf blast while ten genotypes were consistently resistant to neck blast during Kharif 2007 and 2008, indicating that resistance to leaf blast in scented rice cultures is more common than neck blast. Seven genotypes namely, HKR 04-487, HKR 05-436, HKR 05-476, Haryana Mahak-11, PAU 3237-1-B-B-19, PAU 3237-1-B-B-20 and PAU 3237-1-B-B-22 were found consistently resistant to both leaf and neck blast phases during both the years. On the basis of mean data of Kharif 2000 and 2001, carpropamid and tricyclazole were found to be the most promising fungicides in reducing the neck blast incidence followed by kasugamycin and epoxiconazole + carbendazim. However, carbendazim 12% + mancozeb 63% had no significant effect on disease incidence. In addition, kresoxim methyl at 1.5 ml/l and azoxystrobin at 1.0 ml/l were also found highly effective against neck blast and statistically on par with standard fungicide tricyclazole during Kharif 2002 to 2005. The combination treatments of both the fungicides (tricyclazole and iprobenphos) and insecticides (indoxacarb and cartap hydrochloride) were biologically as effective as their individual treatments against neck blast, leaf folder and stem borer of rice, respectively during Kharif 2006 and 2007 along with corresponding increase in grain yield of Taraori Basmati. Tricyclazole alone and in combination with insecticides proved better than iprobenphos alone and in combination with insecticides.